Methyl Ester Sulfonate (MES) Surfactant Production from Waste Cooking Oil (WCO) with Microwave Technology - Qadariyah, Lailatul; Ryvalda, Dhea Septyanonie; Aditama, Narendra Yudha; Aswie, Viqhi; Mahfud, Mahfud (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Traction Energy Asia 2020 reported that 3 million kilolitres of WCO were collected in Indonesia in 2019, 1.6 million kilolitres from urban households. WCO poses risks due to common reuse or disposal. Repurposing for MES surfactant is vital. Hence, this study aims to produce an MES surfactant from WCO feedstock using NaHSO3 as a microwave-assisted reactant by observing the influence of variables such as reactant mole ratio, catalyst concentration, sulfonation reaction time, and microwave power. The adsorption method involves vacuum filtration of WCO to remove impurities, mixing with activated carbon, and settling before a second filtration. Transesterification transforms WCO into methyl ester through mixing with methoxide solution with a molar ratio of methanol to WCO of 1:9 and a 1 wet% NaOH catalyst based on WCO, followed by washing and drying. Sulfonation involves reacting methyl ester with NaHSO3 (1:1, 1:2, 1:3, 1:4) and CaO catalyst (1%, 1.5%, 2%, 2.5%). The reaction occurs in a microwave at power variations of 300, 450, 600, and 750 Watts, as well as with variations in time of 20, 30, 40, 50, and 60 minutes. After that, it ends with purifying and neutralizing to produce MES. The optimal conditions for MES production are a 1:2 molar ratio of reactants, 1.5% CaO catalyst concentration, 20 minutes, and 450 W, yielding 48.06%. MES characteristics: pale yellow color, density of 0.859 g/cm3, viscosity of 1.780 cSt, and surface tension of 32.62 dyne/cm. FTIR analysis confirms sulfonic acid groups at 1195.27 cm−1 and 1169.1 cm−1 wavelengths.